Determining the functions of the pre-Old English runic inscriptions - Higgs, Jasmin (2025)
This thesis offers a comprehensive analysis of the pre-Old English runic corpus (PrOERC)—runic inscriptions from Britain between c. 400 and 650 AD—to investigate the functions of the runic script. Two overarching research questions guide this study: what are the functions of runic script, and how can those functions be identified? Previous research has largely approached these inscriptions from a neo-Grammarian perspective, focusing on phonological, morphological, and syntactic analysis to determine meaning. This approach has led to uneven results: while some inscriptions could be ‘read’ and their functions inferred, others, particularly the non-lexical texts that make up nearly a third of the corpus, could not be analysed in the same way. Non-lexical inscriptions do not form words and, as such, were often excluded from functional interpretation. The field of runology, the study of runic inscriptions, has recently embraced more context-focused methodologies, including semiotics, sociolinguistics, and pragmatics. This thesis evaluates the applicability of pragmatics as a methodological framework for analysing runic inscriptions, concluding that while pragmatics is a valuable tool, it requires methodological adaptation for this purpose. The study employs a pragmatics-informed approach, dividing its analysis into two complementary areas: linguistic analysis and contextual analysis. The linguistic analysis focuses on lexical inscriptions, identifying formulae based on their structural patterns and assigning communicative functions accordingly. The contextual analysis applies pragmaphilology, a methodology that considers contextual factors such as the roles of the text producer and receiver to determine function. Both lexical and non-lexical inscriptions undergo this contextual examination. This thesis reaches significant conclusions about the functions of inscriptions within the PrOERC. Lexical texts exhibit a variety of functions, typically expressed through formulae dominated by personal names. These formulae often reflect the relationship between the rune-bearing object and the individual(s) mentioned in the text. Non-lexical texts, on the other hand, derive their functions primarily from their interaction with the rune-bearing object, mimicking the functions of lexical texts in similar contexts. The findings underscore the necessity of a context-forward analysis for each inscription to fully understand the functions of runic script in the corpus.